A Meta-Analisis of Correlation between Diarrhea and Stunting in Children Under Five - Reza Ramadhana Tahta Firmansyah; Bhisma Murti; Hanung Prasetya (Journal of Epidemiology and Public Health, 2023)
Background: Diarrhea is an infectious disease that can cause children to experience appetite disturbances, resulting in reduced nutritional intake, while the nutrients consumed also fail to be properly absorbed by the body. If this condition is not balanced with appropriate food intake, it can have an impact on cognitive development disorders and height growth, namely stunting. This study aimed to determine whether there was a relationship between a history of diarrhea and the incidence of stunting in toddlers, through a meta-analysis of primary studies conducted by previous authors.Subjects and Method: This study was conducted using a systematic review and meta-analysis with PICO namely, Population: under five, Intervention; diarrhea, comparison: no diarrhea, outcome: stunting. By searching for articles in 2 databases, namely PubMed and Google Scholar, which were published from 2017 to 2022, following keywords "Diarrhea" AND "Stunting" AND "adjusted Odds Ratio" OR "aOR". The included article is a full-text cross-sectional study design for 2017-2022 and reports the adjusted odds ratio (aOR) in multivariate analysis. Articles were selected using prism flow with inclusion criteria, namely, and data analysis using the Review Manager 5.3 application.Results: In total there were 9 articles using a cross-sectional study design with a total sample of 69,549 children under five from Ethiopia, Uganda, Indonesia, Pakistan which had been carried out systematic review and meta-analysis. The data that has been processed shows that toddlers with a history of diarrhea have a risk of experiencing stunting 1.21 times compared to toddlers without a history of diarrhea (aOR= 1.57; 95% CI= 1.20 to 2.05; p< 0.001).Conclusion: Toddlers with a history of diarrhea have a risk of experiencing stunting compared to toddlers without a history of diarrhea. Keywords: diarrhea, stunting, toddlers Correspondence:Reza Ramadhana Tahta Firmansyah, Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah. Email: ramadhanatahta@gmail.com. Mobile: +6282228390930.